Synthesis of Dihydropyrano[3,2-c]pyrazoles via Double Bond Migration and Ring-Closing Metathesis - Yoshihide Usami; Kodai Sumimoto; Azusa Kishima; Yuya Tatsui; Hiroki Yoneyama; Shinya Harusawa (Molecules, 2019)
Three types of pyrazole-fused heterobicycles, i.e., 1,5-, 1,7-, and 2,5-dihydropyrano[3,2-c]pyrazoles, were synthesized from 4-allyloxy-1H-pyrazoles. A sequence of the Claisen rearrangement of 4-allyloxy-1H-pyrazoles, ruthenium-hydride-catalyzed double bond migration, O-allylation, and ring-closing metathesis was employed in this study.